Проблеми формування концепції інноваційного розвитку промисловості України - Гринько, Т.В. (Економіка промисловості, 2013)
Розглянуто питання проблем регулювання інноваційного розвитку у промисловості України. Визначено ряд загроз адаптації інноваційного розвитку держави до умов взаємодії з інноваційним потенціалом інших країн. Сформовано основні причини виникнення цих проблем. Також розглянуто основні напрацювання та програми в державному формуванні інноваційної політики у промисловості.
Ключові слова: інноваційний розвиток, промисловість України, машинобудування, інфраструктура. Рассмотрены вопросы проблем регулирования инновационного развития промышленности Украины. Определен ряд угроз адаптации инновационного развития государства к условиям взаимодействия с инновационным потенциалом других стран. Сформированы основные причины возникновения этих проблем. Также рассмотрены основные наработки и программы в государственном формировании инновационной политики в промышленности.
Ключевые слова: инновационное развитие, промышленность Украины, машиностроение, инфраструктура. The article considers the control problems of innovation development in the industry of Ukraine. A number of threats to the adaptation of innovation development of the country to the terms of interaction with the innovation potential of other countries are defined. The main causes of these problems are formed. Also the principal developments and programs in government formation of the innovation policy in industry are considered.
This research analyzes the current development of innovation processes in the domestic industry and found that it is at a rather low level. This is evidenced by the low rates of innovation activity and volume of expenses on technological innovations and their effectiveness, poor use of scientific potential of the country, lack of innovation infrastructure. It is established that the independence and initiative of enterprises in promoting innovations are paramount. At the same time taking into account the tight nature of the economic reforms carried out it is proved that the indifferent attitude of the legislature to the flow of innovation processes seems disastrous. Mechanical engineering requires state support and laws that provide real guarantees and incentives for domestic and foreign investors in innovation activity.
Keywords: innovation development, industry of Ukraine, mechanical engineering, infrastructure.